Prospective evaluation of sequential treatment of sclerotic chronic graft versus host disease with rituximab and nilotinib. (October 2018) - Wagen, Lotte; Boome, Liane; Schiffler, Marleen; Nijhof, Inger; Schoordijk, Marieke; Dorp, Suzanne; Dijk, Marijke; Raymakers, Reinier; Petersen, Eefke; Witte, Moniek; Jong, Niels; Bellido, Mar; et al.
Abstract Sclerotic chronic graft vs. host disease (cGVHD) still has a large impact on morbidity and mortality after allogeneic hematopoietic stem cell transplantation (HSCT). We performed the first prospective study to test whether sequential therapy of the anti-CD20 antibody rituximab followed by 6 months treatment with tyrosine kinase inhibitor nilotinib is a favorable treatment strategy for patients with sclerotic cGVHD. Twenty-nine patients were included, 24 were available for analysis. We observed objective responses in 71% of patients (two patients CR, 15 patients PR). Moreover, two out of five patients suffering from severe ulcerations showed complete resolution of ulcers. Observed responses lasted until the end of study follow-up. The majority of responding patients could reduce daily corticosteroid dose with more than 50%. Furthermore, CD5+ B-cells are significantly lower (p  = 0.007) in responding patients at baseline, proposing a new biomarker predictive for response. In conclusion, sequential treatment of rituximab followed by nilotinib associates with a very high response rate in this difficult to treat patient population. CD5+ B-cells could assist in guiding treatment choices and might be a first step toward more personalized cGVHD treatment. This trial was registered at the Dutch clinical trial registry as NTR1222.